2005
DOI: 10.4315/0362-028x-68.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella Transformed To Express Green Fluorescent Protein on Italian Parsley as Affected by Processing and Storage

Abstract: To study the effect of processing and storage parameters on the survival of Salmonella on fresh Italian parsley, parsley bunches were dipped for 3 or 15 min in suspensions that were preequilibrated to 5, 25, or 35ЊC and inoculated with Salmonella transformed to express enhanced green fluorescent protein. Loosely attached and/or associated, strongly attached and/or associated, and internalized and/or entrapped Salmonella cells were enumerated over 0, 1, and 7 days of storage at 25ЊC and over 0, 1, 7, 14, and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…and E. coli O157:H7, have been found to be associated with the natural openings in the plant surface in a number of studies (Dong, Iniguez, Ahmer, & Triplett, 2003;Duffy et al, 2005;Gomes et al, 2009;Itoh et al, 1998;Kroupitski et al, 2009;Shaw et al, 2008). The same preferential localization of the bacteria can be found in artificially induced wounds (Burnett, Chen, & Beuchat, 2000) and naturally occurring lesions (Brandl & Mandrell, 2002;Han, Linton, Nielsen, & Nelson, 2000), as well as with physical damage caused by plant pathogens (Beuchat, Scouten, Allen, & Hussey, 2003).…”
Section: Routes Of Internalizationmentioning
confidence: 77%
“…and E. coli O157:H7, have been found to be associated with the natural openings in the plant surface in a number of studies (Dong, Iniguez, Ahmer, & Triplett, 2003;Duffy et al, 2005;Gomes et al, 2009;Itoh et al, 1998;Kroupitski et al, 2009;Shaw et al, 2008). The same preferential localization of the bacteria can be found in artificially induced wounds (Burnett, Chen, & Beuchat, 2000) and naturally occurring lesions (Brandl & Mandrell, 2002;Han, Linton, Nielsen, & Nelson, 2000), as well as with physical damage caused by plant pathogens (Beuchat, Scouten, Allen, & Hussey, 2003).…”
Section: Routes Of Internalizationmentioning
confidence: 77%
“…Surface disinfection by immersion in an AgN03 solution has been used to eliminate surface pathogens on leafy greens, enabling assessment of internalization by enrichment and plate counts (12,14). Others have also used chlorinated water for surface disinfection (9,17,26). In our study, compared with AgN03, there was a slight advantage to using chlorinated water because of the lower number of leaves giving positive prints (Table 1) and fewer viable cells detected on leaf surfaces (Fig.…”
Section: Selection Of Surface Disinfection Methodmentioning
confidence: 62%
“…Takeuchi and Frank (31) demonstrated that soaking freshcut lettuce in a suspension of E. coli 0157:H7 (9 log CFU/ ml) at 4°C resulted in a greater number of cells penetrating into cut surfaces than at higher temperatures. Another report, however, showed that a temperature differential did not promote Salmonella internalization into Italian parsley (9). The issue of internalization is of special concern during postharvest hydrocooling, whereby water is used to cool produce.…”
mentioning
confidence: 97%
“…5 presents a multilabeling example where a mixture of bacteria preferentially occupies the interstitial space between the caseins and the fat in the matrix. Salmonella was shown to preferentially colonize the stomata and cracks of the waxy cuticle of parsley leaf (no pathogens were detected near the leaf edge or on intact leaf surface) (Duffy et al, 2005). In meat products, Yersinia enterolitica was evidenced in deep structure of hair like procine skin follicles (Morild et al, 2011) while E. coli O157:H7 was shown to adhere preferentially to fibril-forming collagens I and IIII of the muscle extracellular matrix (Chagnot et al, 2013).…”
Section: Direct Visualization Of Microorganisms In Complex Food Matricesmentioning
confidence: 98%